The feasibility of flipbook-based Wawasan Nusantara teaching materials in citizenship learning - Yunita, Sri; Sugiharto, Sugiharto; Hadiningrum, Sri; Ivanna, Julia; Firdaus, Alif (Universitas Negeri Yogyakarta, 2025)
Learning media has a significant influence on learning outcomes. Using appropriate media can increase motivation, understanding, retention, practical skills, accessibility and collaboration in learning. However, the effectiveness of media also depends on design, implementation and learning context. Therefore, educators need to choose and design media that suits the goals and needs of students. This research aims to (1) produce flipbook-based Wawasan Nusantara teaching material products and (2) Understand the feasibility of flipbook-based Wawasan Nusantarateaching materials. The development model used in this research is ADDIE. The needs analysis results of lecturers and students show that the need for flipbook-based Indonesian insight teaching materials is enormous. The material expert validation results were 98.46% in the outstanding category, and the media expert validation was 90.58% in the exceptional category. The results of student assessments regarding the acceptability of teaching materials include very high acceptability, with a score of 4.94. So, it can be concluded that flipbook-based Indonesian language insight teaching materials are suitable for citizenship education learning. Teachers and students can use flipbook-based Indonesian language insight teaching materials as teaching materials in learning activities to help improve student learning.